Analisis Kepuasan Masyarakat terhadap Pelayanan Publik Pemberian Izin Mendirikan Bangunan di Kota Jayapura (Suatu Studi di Dinas Penanaman Modal dan Perizinan Terpadu Satu Pintu) - Ariastuti, Ni Luh Putu Nia (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
This studi aims to analyze the Public Satisfaction of Public Service Providing IMB in Jayapura City. Researchers analyzed using 14 indicators based on the KEPMENPAN regulation Number 25 of 2004 concerning Guidelines for Preparation of Comunnity Satisfaction Index consisting of service procedure, service requirements, clarity of service officers, discipline of service officers, responsibility of officers, ability of officers, speed of service, fairness of service, courtesy and friendliness of staff, the fairness of costs, certainty of costs, certainty of schedule, comfort of the environment and security of service. As for the type of research used is descriptive research with a qualitative approach. The results showed that 14 indicators of SMIs used 5 of them identified the quality of public services in the DPMPTSP Jayapura City including service requirements, service ability, speed of service, certainty of schedule and comfort of the service environment. For this reason, there is still a need to improve and improve the quality of public services in DPMPTSP Jayapura City.